Untold Stories: Indigenous Knowledge Beyond the Changing Arctic Cryosphere - Eerkes-Medrano, Laura; Huntington, Henry P. (Frontiers in Climate, 2021)
Abstract Scientific attention to climate change in the Arctic has spurred extensive research, including many studies of Indigenous knowledge and the effects of climate change on Indigenous peoples. These topics have been reported in many scientific papers, books, and in the IPCC’s 2019 Special Report on the Ocean and Cryosphere in a Changing Climate (SROCC), as well as attracting considerable interest in the popular media. We assembled 56 peer-reviewed publications concerning Arctic Indigenous peoples and climate change for the SROCC, and have further reviewed 25 papers discovered through a subsequent literature search. A closer look at these 81 papers reveals additional emphases on economics, culture, health and mental health, policy and governance, and other topics. While these emphases reflect to some degree the perspectives of the Indigenous peoples involved in the studies, they are also subject to bias from the interests and abilities of the researchers involved, compounded by a lack of comparative research. Our review shows first that climate change does not occur in isolation or even as the primary threat to Indigenous well-being in the Arctic, but the lack of systematic investigation hampers any effort to assess the role of other factors in a comprehensive manner; and second that the common and perhaps prevailing narrative that climate change spells inevitable doom for Arctic Indigenous peoples is contrary to their own narratives of response and resilience. We suggest that there should be a systematic effort in partnership with Indigenous peoples to identify thematic and regional gaps in coverage, supported by targeted funding to fill such gaps. Such an effort may also require recruiting additional researchers with the necessary expertise and providing opportunities for inter-regional information sharing by Arctic Indigenous peoples. As researchers who are visitors to the Arctic, we do not claim that our findings are representative of Indigenous perspectives, only that a more accurate and comprehensive picture of Arctic Indigenous peoples’ knowledge of and experiences with climate change is needed. Our analysis also reflects some of the SROCC knowledge gaps and the conclusions provide suggestions for future research.